Encyclopedia of Ukraine. - Struk, Danylo Husar, 1940-1999 (University of Toronto Press, 1993)
Over thirty years in the making, the most comprehensive work in English on Ukraine is now complete: its history, people, geography, economy, and cultural heritage, both in Ukraine and in the diaspora.